1976
DOI: 10.1073/pnas.73.6.2096
|View full text |Cite
|
Sign up to set email alerts
|

Human and murine phosphorycholine-binding immunoglobulins: conserved subgroup and first hypervariable region of heavy chains.

Abstract: The NH2-terminal 36 residues of the heavy chain and the NH-terminal 40 residues of the light chain from a human Waldenstr6m's IgM with binding activity for phosphorylcholine (phosphocholine) are compared with the published sequences of five mouse IgA myeloma proteins with the same activity. An extensive structural similarity, i.e., 3 amino acid interchanges within framework residues, and one in the hypervariable region, is noted between the heavy chains of both species. The light chains, however, show a consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…An alternative hypothesis (Capra et al 1977) is that the hypervariable regions provide specificities which are useful for the survival of the animal and have therefore been preserved in the germ line; i.e., that the DNA sequences coding for these hypervariable regions existed before the divergence of VK subgroups. Relevant to this argument is a recent publication of Riesen et al (1976) who determined the N-terminal 36 residues of the H chain of a human "WaldenStrom's IgM with the capacity to bind phosphorylcholine. The sequence was compared with sequences of five mouse IgA myeloma proteins, having the same antibody activity, which had been worked out by Barstad et al (1974).…”
Section: Structural Studies Of a Cross-reactive Idiotype Associated Wmentioning
confidence: 99%
“…An alternative hypothesis (Capra et al 1977) is that the hypervariable regions provide specificities which are useful for the survival of the animal and have therefore been preserved in the germ line; i.e., that the DNA sequences coding for these hypervariable regions existed before the divergence of VK subgroups. Relevant to this argument is a recent publication of Riesen et al (1976) who determined the N-terminal 36 residues of the H chain of a human "WaldenStrom's IgM with the capacity to bind phosphorylcholine. The sequence was compared with sequences of five mouse IgA myeloma proteins, having the same antibody activity, which had been worked out by Barstad et al (1974).…”
Section: Structural Studies Of a Cross-reactive Idiotype Associated Wmentioning
confidence: 99%
“…The A.S. H chain, however, belongs to the VHIII sub group. An association between variable region sub group and specificity has already been described in other systems [1,3,18,23,24], This repeated finding of an association between the relatively invariant re sidues (framework) of the variable region and antigen binding specificity suggests that not only the hyper variable regions but also the framework play an im portant role in the construction of the three-dimen sional combining site. However, it may also be anti cipated that genetic factors are responsible for this finding.…”
Section: Discussionmentioning
confidence: 82%
“…The activity is restricted to the Fab part of the molecule [17,36] and it is therefore thought to be a true antibody activity. Studies on monoclonal human immunoglobulins with binding activity against cold agglutinins or yglobulins or against phosphorylcholine have pro vided valuable information about the idiotypic pro perties and the relation between the primary structure of the polypeptide chains and the binding specificity [15,16,23,24,34]. These studies have indicated an ex tensive cross-reactivity within groups of anti-y-globulins and cold agglutinins and a striking association between the immunoglobulin class, subclass or var iable region subgroup and the binding specificity.…”
Section: Introductionmentioning
confidence: 99%
“…If, in fact, the shared, neutral bands in rat anti-PC sera, the TEPC-15 group of mouse myeloma proteins, and possibly the induced anti-PC antibodies in guinea pigs are all products of germ line genes, it should be possible to determine whether these rodent anti-PC germ-line genes share a common origin through structural analysis of the proteins produced. Along these lines, Riesen et al (1976) have recently shown that a human PC-binding macroglobulin differs by only 4 out of 36 amino acids in the amino-terminal sequence of the heavy chains when compared to 5 mouse IgA myeloma proteins with similar binding specificity. This remarkable similarity between human and mouse proteins may either reflect strong structural constraints upon any immunoglobulin in order to maintain PC specificity or it may reflect a common evolutionary origin.…”
Section: Discussionmentioning
confidence: 99%